Aspectos psicossociais do viver com diabetes Mellitus na promoção do autocuidado - Sumaya Giarola Cecilio; Célia Luciana Guedes Barbosa Brasil; Camila Pacheco Vilaça; Samara Mariana Ferreira da Silva; Elisângela da Cruz Vargas; Heloísa de Carvalho Torres (Universidade Federal do Ceará, 2016)
Objective: to understand the psychosocial aspects of living with diabetes mellitus. Methods: a study qualitative made with 16 patients with diabetes mellitus type 2. The data were collected through telephone calls using a semi-structured script approaching the care in health, barriers and family support, analyzed by Bardin's content. Results: two categories emerged related to the practice of self-care: Self-care, containing three sub-categories: diet, physical activity and emotional aspects and support networks. Conclusion: the results of the study showed the importance of understanding the emotional aspects and attitudes of patients regarding educational practices for self care, in order to establish strategies to prevent and control the disease.